Case Report: Giant paratesticular liposarcoma was resected and refused radical orchiectomy - Zou, Qianming; Gan, Shu; Li, Yuan; Huang, Qinzhan; Wang, Shusheng; Li, Siyi; Gu, Chiming (Frontiers in Oncology, 2023)
Paratesticular liposarcoma (PLS) causes scrotal mass changes, rarely in the urinary system. Before surgery, PLS causes scrotal mass changes that are difficult to distinguish from other causes. There has been a report of a giant paratestis liposarcoma resection and refusal to undergo orchiectomy. A 65-year-old man presented with finding the left scrotal mass after 2 years. Physical examination showed that the left scrotal mass was obviously difficult to retract. Pelvic CT showed that the left scrotal mass and flaky fat density shadow accompanied with left inguinal hernia. During surgery, laparoscopic exploration was performed to rule out inguinal hernia, and a scrotal exploration was also performed concurrently. The intraoperative frozen pathology considered lipogenic tumor, and the patient's wife refused to undergo simultaneous left radical orchiectomy. Later the mass was completely removed, and postoperative pathology confirmed paratestis liposarcoma. During a 15month routine follow-up, the tumor did not recur locally or metastasize distantly. PLS should be focused on early diagnosis and treatment, preoperative examinations and postoperative pathology should be combined, and highly personalized treatment will be implemented.